STRATEGIC MANAGEMENT AND COMMUNITY-BASED DEVELOPMENT IN OPTIMIZING BUMDES NUSATAPI, MORELLA VILLAGE, CENTRAL MALUKU - Normawati, Normawati; Fadli, Zul; Pical, Khusnul Khatimah (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the management of the Village-Owned Enterprise (BUMDes) Nusatapi in Morella Village, Leihitu District, Central Maluku Regency, as well as the supporting and inhibiting factors in its implementation. BUMDes was established to increase Village Original Revenue (PAD) and improve community welfare by optimizing the village’s abundant natural resources, especially in the agriculture, fisheries, and tourism sectors. However, the management of BUMDes Nusatapi has not yet been fully optimized. This is due to limited capital, lack of training for management personnel, and inadequate infrastructure. These issues are critical because the village’s significant economic potential has not been fully utilized to promote local economic growth. This study uses a descriptive qualitative approach, collecting data through interviews, observations, and documentation. The findings indicate that the main challenges in managing BUMDes are limited business capital and the low quality of human resources. On the other hand, abundant natural resources and community support are key supporting factors. This study recommends increasing budget allocation and developing human resource capacity to optimize BUMDes management. This research is essential as it provides insights into how BUMDes can better contribute to improving community welfare through more effective management of local resources.